Coral Stone Installation On the Substation Grounding System In Limestone - Janardana, I Gusti Ngurah; Wijaya, I Wayan Arta (Journal of Electrical, Electronics and Informatics, 2022)
The step voltage and touch voltage exceed the maximum limit due to overcurrent to the ground flowing in the equipment grounding area which is dangerous for the equipment and people in the vicinity. The ground at the switchyard location is filled with coral above the ground level. The purpose of this study was to determine the thickness of coral in the grounding system of switchyard equipment in calcareous soil. The analytical method of this research is to calculate the results of the thickness of the coral to get the standard value of IEEE-80-2013. The result of this research is that the installation of 0.15 meters of coral when wet or dry produces the best step voltage and touch voltage values when compared to the thickness of 8 cm (0.08 meters) of coral stone to 14 cm (0.14 meters)